Role of the Tyrosine Phosphatase SHP-2 in Mediating Adrenomedullin Proangiogenic Activity in Solid Tumors - Sigaud, Romain; Dussault, Nadège; Berenguer-Daizé, Caroline; Vellutini, Christine; Benyahia, Zohra; Cayol, Mylène; Parat, Fabrice; Mabrouk, Kamel; Vázquez, Ramiro; Riveiro, Maria E.; Metellus, Philippe; Ouafik, L’Houcine (Frontiers in Oncology, 2021)
VE-cadherin is an essential adhesion molecule in endothelial adherens junctions, and the integrity of these complexes is thought to be regulated by VE-cadherin tyrosine phosphorylation. We have previously shown that Adrenomedullin (AM) blockade correlates with elevated levels of phosphorylated VE-cadherin (pVE-cadherinY731) in endothelial cells, associated with impaired barrier function and a persistent increase in vascular endothelial cell permeability. However, the mechanism underlying this effect is unknown. In this article, we demonstrate that the AM-mediated dephosphorylation of pVE-cadherinY731 takes place through activation of the tyrosine phosphatase SHP-2, as judged by the rise of its active fraction phosphorylated at tyrosine 542 (pSHP-2Y542) in HUVECs and glioblastoma-derived-endothelial cells. Both pre-incubation of HUVECs with SHP-2 inhibitors NSC-87877 and SHP099 and SHP-2 silencing hindered AM-induced dephosphorylation of pVE-cadherinY731 in a dose dependent-manner, showing the role of SHP-2 in the regulation of endothelial cell contacts. Furthermore, SHP-2 inhibition impaired AM-induced HUVECs differentiation into-cord-like structures in vitro and impeded AM-induced neovascularization in in vivo Matrigel plugs bioassays. Subcutaneously transplanted U87-glioma tumor xenograft mice treated with AM-receptors-blocking antibodies showed a decrease in pSHP-2Y542 associated to VE-cadherin in nascent tumor vasculature when compared to control IgG-treated xenografts. Our findings show that AM acts on VE-cadherin dynamics through pSHP-2Y542 to finally modulate cell-cell junctions in the angiogenesis process, thereby promoting a stable and functional tumor vasculature.